Citizen Participation in International Development Law: Grounds, Obstacles and Supporting Ways - Reza Eslami; Negar Reisi (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2017)
International development law, as an international rule maker system which is based on equity and solidarity, seeks to provide equal opportunities for cooperation of all countries in international relations regardless of their economic and social status. In this regard, international cooperation between developed and under developed countries, meaningful, real, and widespread participation of citizens in general, and NGOs, women and indigenous people in particular are the main tools for achieving development. The crucial point here is enhancing and promoting broad, informed and active participation of citizens within the international development law particularly in the fields of poverty reduction and environmental. Since the success of development programs is highly relied on the acceptance of stakeholders, empowerment, creation of opportunities and providing conditions for citizens' participation at all levels of decision making will not only create a ground for effective participation of citizens and fulfillment of human development, but also lead to achievement of sustainable development goals.